Pengelolaan Aktivitas Jaulah Jamaah Tabligh di Kecamatan Bilah Hilir Kabupaten Labuhan Batu - Syarif, Adam; Haikal, Muhammad Fachran; Indonesia, Indonesia (Wardah, 2024)
This study investigates and analyzes the management of Tabling Jamaah Jaulah activities in Bilah Hilir sub-district, Labuhan Batu Regency, North Sumatra. This study employs a qualitative approach and case study method. Data was gathered through interviews, observations, and documentation, with informants including members of the Tabligh, local communities, and sub-district officials. The data was analyzed using data reduction, data presentation, and conclusion. The findings show that Tabligh activities are managed collectively and participative, involving planning, implementation, and evaluation. The management is consistent with the concept of dawah and motivation taught in Islam. The Jamaah Tabligh also preaches using humanist, inclusive, and dialogical strategies and methods, focusing on morals and manners, respecting and appreciating the local community, and inviting rather than forcing. The Jamaah Tabligh also adheres to its six principles, which are Kalimah Thoyyibah, Salat Khusyu wal Khudu, Ilmu and Zikir, Ikraamul Muslimin, Ikhlas and Niyyat, and Dakwah Tabligh. The Jamaah Tabligh has both positive and negative effects and internal and external challenges when preaching. This study suggests methods to improve resources, skills, coordination, discipline, understanding, and proper application of Islamic teachings, as well as overcome existing attitudes, differences, interventions, influences, and slander.